Seroprevalence of human T-Cell Lymphoma/Leukemia virus Type-1 (HTLV-1) Antibodies among blood donors at Ibadan, Nigeria (2017)
Background: Blood transfusion is an efficient mode of transmission of viruses and other infectious agents. Although human T-lymphotropic virus type 1 (HTLV-1) screening of blood donors is already routinely performed in developed countries, there is no routine screening of blood donors in our environment. As HTLV I and II are human retroviruses and are endemic in sub-Saharan African, including Nigeria, there is need to evaluate the burden of HTLV among blood donors in developing countries. Objective: The current study was carried out to determine the prevalence of HTLV I/ II among apparently healthy blood donors at the University College Hospital, Ibadan, Nigeria. Material and Methods: A total of 1,000 consented, apparently healthy blood donors were recruited into a hospital-based cross-sectional study conducted at the Blood bank. 5mL of sera was obtained from each participant and analyzed for antibodies to HTLV-1 using a one-step incubation double-antigen sandwich ELISA (enzymelinked immunosorbent assay) kit. Participants’ sociodemographic characteristics and possible risk factors associated with HTLV-1 infection were assessed using a questionnaire. Statistical analysis of results was done using SPSS version 17. Results: Of the 1000 blood donors, 942 (94.2%) were male, while the average age of the blood donors was 32.26 (±8.96) years. Thirty-two (3.2%) of the blood donors tested positive for HTLV I/II antibodies. All the positive cases were males. The major risk factors for HTLV I/II seropositivity among participants include; age less than 30 years, single status and previous history of blood transfusion. Other significant risk factors include; first time commercial blood donors and drug addiction. . Conclusion: This study documents the Seroprevalence of HTLV I/II infection in our environment, thus highlighting the need for large scale multi-centered studies and routine screening of blood donors for HTLV-1 infection.